Scientific and Religious Outlook - Radzhabov, Osman; Lobacheva, Zoya; Bagliyeva, Zarema; Bigayeva, Zarema; Magomedova, Uzumei; Mirimova, Afisat; Mammayev, Madinat (Journal of History Culture and Art Research, 2017)
In this article, the problem of scientific ratio and religious outlook is analyzed. Features of scientific outlook, in particular the fact that it is formed on the basis of scientific knowledge are emphasized. The objective reality is reflected in the consciousness of people in the form of fantastic images in religious outlook. As the religion and religious doctrines are based on belief, and belief, as we know, assumes the emotional and mental condition of the person accepting statements of basic provisions of the religious doctrine. For religion, these provisions are firm and eternal. Unlike religion, the science relies on knowledge and reason of the person, forms a scientific picture of the world, which is described in the form of scientific laws, categories and principles. Today, science and religion play an important role in the outlook formation.